RELATIONSHIP PRINCIPAL LEADERSHIP TO WORK MOTIVATION, MORALE TEACHER AND TEACHER PERFORMANCE OF STATE JUNIOR HIGH SCHOOLS - Noor, Syamsudin; Wahyu, Wahyu; Suhaimi, Suhaimi (Journal of K6, Education and Management, 2019)
This study aims to Describe the Principal Leadership, work motivation, morale and teacher performance in State Middle Schools in the East Banjarmasin sub-district of Banjarmasin City. This study uses a quantitative approach with descriptive methods. The total population of this study is 122 teachers of SMP Negeri East Banjarmasin, Banjarmasin City. , sampling uses the sample proportional random sampling technique, the data is collected using questionnaires. Hypothesis testing is done using regression test analysis techniques. (1) There is no significant relationship between principals 'leadership and motivation (2) There is no significant relationship between principals' leadership and teacher's morale. (3) Principal leadership is directly related significantly to teacher performance. (4) There is a direct relationship between work motivation and teacher performance (5) There is a significant relationship between work morale and teacher performance The results of this study are expected to be useful in an effort to improve work motivation, morale and teacher performance in carrying out teaching tasks and indirectly improve leadership of the principal itself